Multi-Messenger Astrophysics and the Epistemic Reasons for Cooperative Behavior. - GUZZARDI, LUCA (Centaurus: Journal of the European Society for the History of Science, 2025)
Cooperative phenomena in science are frequently viewed as the result of social forces and material conditions within a given social system of knowledge. In this context, scientific requirements often remain in the background, if not entirely overlooked, in discussions about what motivates cooperation. This paper challenges such interpretations using examples from the history of neutrino astronomy and recent multi-messenger discoveries. Revisiting the hierarchy of models proposed by Suppes (1962), it argues that the ethos of collaboration in multi-messenger astrophysics is primarily driven by epistemic constraints embedded within the models describing typical multi-messenger sources and processes. These constraints necessitate cooperation among multi-messenger astronomers, regardless of other motivations for their collaborative efforts and despite the complexities and challenges involved.